A checklist of the leafhoppers of Iran (Hemiptera: Auchenorrhyncha: Cicadellidae) - Mozaffarian, Fariba; Wilson, Michael R. (Zootaxa, 2016)
A list of Cicadellidae (leafhoppers) of Iran is provided based primarily on literature records from 1902 to the present. In total 390 species are recorded from 13 subfamilies. Ninety three of the recorded species are considered to be endemic to Iran. The current accepted name is given for each species together with synonyms and literature citations relating to Iran. Selenocephalus darei is recognized as a published misspelling for Selenocephalus dareicus Dlabola, 1981. There is no evidence that the Nearctic species Empoasca fabae (Harris, 1841) and Erythroneura comes (Say, 1825) have been found in Iran; previous records appear to have been based on misidentifications. A brief distribution of species within Iran is provided.